2021
DOI: 10.2217/fca-2020-0175
|View full text |Cite
|
Sign up to set email alerts
|

CHA 2 DS 2 -VASc and HAS-BLED Risk Scores and real-world Oral Anticoagulant Prescribing Decisions in Atrial Fibrillation

Abstract: Background: Guidelines indicate that oral anticoagulant (OAC) treatment decisions in atrial fibrillation should be based on a balanced consideration of thromboembolic and bleeding risk. Materials & methods: A retrospective cohort of nonvalvular atrial fibrillation patients were identified. Univariate logistic regression and conditional inference trees were used to quantify the importance of the CHA2DS2-VASc and modified HAS-BLED scores and their individual components on OAC treatment decisions. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…After the introduction of NOACs, which have a high safety profile and do not necessitate monitoring of the INR, they were more likely to be prescribed to the elderly and to patients at increased risk of bleeding. A large retrospective study of a cohort of nonvalvular atrial fibrillation patients revealed that physicians make their treatment decisions based on the patient's individual risk factors, not on the values of the risk scores [18]. Therefore, anticoagulant therapy should be approached with caution in this group, taking into account the benefits and possible side effects.…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of NOACs, which have a high safety profile and do not necessitate monitoring of the INR, they were more likely to be prescribed to the elderly and to patients at increased risk of bleeding. A large retrospective study of a cohort of nonvalvular atrial fibrillation patients revealed that physicians make their treatment decisions based on the patient's individual risk factors, not on the values of the risk scores [18]. Therefore, anticoagulant therapy should be approached with caution in this group, taking into account the benefits and possible side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of AF increases with age; however, the results of studies suggest that older patients (especially those over the age of ≥90 years) with a perceived high risk for bleeding (e.g., chronic kidney disease) are often refused OACs [ 15 ]. A large retrospective study of a cohort of patients with nonvalvular AF revealed that physicians make their treatment decisions on the constellation of patient’s risk factors, such as bleeding risk factors (including drugs and hypertension within the year before diagnosis), age and history of major bleeding, not on values of the risk scores, even though international guidelines do not point to bleeding risk factors as a contraindication to treatment [ 7 ]. In turn, Volgman et al [ 25 ] found that syncope and fall-related injuries are the most frequent causes of non-prescription of OAC among elderly patients (75 years or above).…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant therapy was suggested to be prescribed more frequently in patients with permanent AF compared with patients with paroxysmal AF, even though the guidelines advocate anticoagulation irrespective of AF type [ 32 , 33 ]. In turn, the results of the study performed by Besford et al [ 7 ] demonstrated that bleeding risk factors, including hypertension within one year before diagnosis, age at diagnosis as well as the history of major bleeding, and use of drugs that increase the risk of bleeding in the year before diagnosis were the most important factors in the treatment decision. Similarly, the Health Improvement Network database pointed to very old age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations